The effect of UV light and weather on plastics and elastomers. (Plastics Design Library, 1994)
This handbook is an compilation that illustrates how the elements of weathering affect the properties and characteristics of 89 plastics and elastomers. It is comprised of diverse references, including conference proceedings, test laboratories, materials suppliers, monographs, and trade and technical journals. The information provided ranges from a general overview of the resistance of various plastics and elastomers to weathering (ultraviolet light, moisture, heat) to detailed discussions and test results. At the same time, an effort is made to provide information for many weathering tests and conditions (i.e. outdoor, outdoor accelerated, artificial accelerated, indoor, microbiologic attack, etc.) and material combinations. Results of weathering exposure for more than 80 families of plastics and elastomers are presented in textual, graphical and tabular formats.
Keywords: Plastics -- Deterioration.; Elastomers -- Deterioration.; Plastics -- Effect of radiation on.; Elastomers -- Effect of radiation on.; Ultraviolet radiation.; elektronické knihy; electronic books